Effects of Different Levels of Urea and Superphosphate Fertilizer in Some Growth Characters and the Yield of Fenugreek plant - Twaij, S. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An experiment was conducted in pots with 4 Kg soil per pot in the green house of Biology department, College of Education (Ibn Al-Haithum), university of Baghdad, the growing season of (2008-2009), to study the effects of four levels of urea (0, 0.1, 0.2, 0.4) g/pot, that equivalent to (0, 100, 200 and 400) Kg/ha. Also three levels of superphosphate fertilizer (0.2, 0.1, and 0) g/pot, that equivalent to (200, 100, and 0) Kg/ha were added to the local yields components. The result showed that the high level of both fertilizer (400 Kg urea/ha and 200 Kg superphosphate/ha) caused a significant increase in number of pods/plant, dry weight of pods, the weight of 100 seeds and the weight of all seeds/plant, with a significant decrease in the character of  the relative yield.